2010
DOI: 10.1159/000321536
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Different Methods to Assess Erosive Lesion Depths and Progression in vitro

Abstract: The aim of this study was to compare the precision and accuracy of 5 different methods applied to assess surface substance loss or changes in surface microhardness (SMH) on the same enamel surfaces after repeated acid exposures. Ground specimens from human molars were exposed to 0.01 M HCl (pH 2.2) for 6 min × 2 and measurements performed 3 times to estimate precision. The accuracies (systematic errors) were calculated against the manufacturer’s calibration standard. Lesion depth progression was from 94 to 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
19
0
5
Order By: Relevance
“…Although the determination of lesion depth by use of calcium loss is an indirect method, it was shown to be a reliable method for analysing the progression of etch depth related to successive acid exposures on the same enamel surfaces. 28 It was also demonstrated that this method was comparable to the direct methods such as white light interferometry and light profilometry. 28 If one considers the definition of caries as a demineralization/remineralization imbalance leading to net mineral loss, mineral loss should be the parameter of a carious lesion that should be measured.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although the determination of lesion depth by use of calcium loss is an indirect method, it was shown to be a reliable method for analysing the progression of etch depth related to successive acid exposures on the same enamel surfaces. 28 It was also demonstrated that this method was comparable to the direct methods such as white light interferometry and light profilometry. 28 If one considers the definition of caries as a demineralization/remineralization imbalance leading to net mineral loss, mineral loss should be the parameter of a carious lesion that should be measured.…”
Section: Discussionmentioning
confidence: 87%
“…28 It was also demonstrated that this method was comparable to the direct methods such as white light interferometry and light profilometry. 28 If one considers the definition of caries as a demineralization/remineralization imbalance leading to net mineral loss, mineral loss should be the parameter of a carious lesion that should be measured. However, considering the direction of progression and the relationship between the defence reaction of the tooth and depth of progression, depth of mineral loss may be as relevant as volume of mineral loss.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have quantified the characteristics of enamel exposed to erosive wear using various methods. A white light interferometer (WLI) is a type of computerized optical interference microscopy that has been used to analyze substance loss of enamel after acid exposure in laboratory and in situ dental erosive studies 9,10) . It has been shown that WLI is able to operate with an accuracy down to 20 nm for measurements on polished enamel surfaces 10) .…”
Section: Introductionmentioning
confidence: 99%
“…A white light interferometer (WLI) is a type of computerized optical interference microscopy that has been used to analyze substance loss of enamel after acid exposure in laboratory and in situ dental erosive studies 9,10) . It has been shown that WLI is able to operate with an accuracy down to 20 nm for measurements on polished enamel surfaces 10) . Moreover, nanoindentation is a useful method to detect very small changes in surface hardness at the early stages of in situ eroded enamel.…”
Section: Introductionmentioning
confidence: 99%